Molecular detection of Lactobacillus acidophilus in the dental plaque of Iraqi patients - Jasim, Anfal Ihsan; Alwarid, Rasha Jasim; Jassim, Sura Dakhil (Pharmakeftiki, 2025)
Microbial colonization of both hard and soft oral surfaces constitutes the primary component of dental plaque. The probiotic strain Lactobacillus acidophilus has been implicated in the formation of dental plaque, with its heightened acidogenicity considered a potential adverse effect. This study aimed to investigate the presence of L. acidophilus within the oral biofilm of periodontally healthy individuals. A total of 90 subjects aged 20–40 years were enrolled. Specimens were collected from patients attending a private dental clinic in Hillah, Iraq, seeking comprehensive dental and periodontal evaluation between October 2022 and February 2023. Both male and female participants were included. The detection of L. acidophilus was performed using polymerase chain reaction (PCR) and conventional culturing methods. Among the 42 samples analysed via culture, only 2 (4.8%) tested positive. In contrast, PCR identified L. acidophilus in 4 out of 48 samples (8.3%). Although PCR is widely regarded as the most sensitive and specific method for bacterial identification, its accuracy may be compromised by technical variables such as excessive sample dilution.